Low-level laser therapy combined with postural correction exercises on postpartum sacroiliac joint pain: a randomised controlled trial - El-Shafei, Manal A.; Abd Allah, Dina S.; Elmasry, Donia M.; Mohamed, Mohamed F.; Hamdy, Hend A. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Sacroiliac joint (SIJ) pain is a common problem that aﬀects women during and after pregnancy and restricts their daily activities. It can be treated with various physiotherapy interventions, including exercises, patient education, and pain relief modalities, such as laser therapy. A randomised controlled trial study conducted between May and September 2022 to deter-mine the eﬃcacy of low-level laser therapy combined with posture correction exercises on postpartum sacroiliac pain.Methods. Sixty postpartum women complaining of SIJ pain, six weeks following vaginal delivery, their ages between 25 and 35 and their BMI not exceeding 30 kg/m2, participated in this study. They were equally and randomly assigned into three groups: A, B and C. Group A received low-level laser therapy, group B received posture correction exercises, and group C received combined low-level laser therapy and posture correction exercises. Pain level was assessed via the Visual Analogue Scale, and the pressure algometry was used to detect pain pressure threshold. Function disability was evaluated by the Oswestry Disability Index. All measurements were taken before and after 6 weeks of the intervention in all groups.Results. MANOVA was used to detect the diﬀerence between treatments and time, and multiple pairwise comparisons with the Bonferroni correction were used to clarify within- and between-groups diﬀerences. The within-group comparison showed signiﬁcant improvement in all variables within each group as p < 0.05. Between-groups post-treatment, there was a signiﬁcant diﬀerence between groups A and B and groups B and C for all variables as p < 0.05, but there were no statistically signiﬁcant diﬀerence between groups A and C for any variables (p > 0.05) except function, with p < 0.05.Conclusions. Based on the study results, adding low-level laser therapy to posture correction exercises in the treatment protocol of postpartum SIJ pain provides better pain relief and functional improvement than when each intervention is used separately.
Keywords: low-level laser therapy; postpartum period; pain management; sacroiliac joint